2021
DOI: 10.1007/s00415-021-10497-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SARS-CoV-2 on reperfusion therapies for acute ischemic stroke in Lombardy, Italy: the STROKOVID network

Abstract: Whether and how SARS-CoV-2 outbreak affected in-hospital acute stroke care system is still matter of debate. In the setting of the STROKOVID network, a collaborative project between the ten centers designed as hubs for the treatment of acute stroke during SARS-CoV-2 outbreak in Lombardy, Italy, we retrospectively compared clinical features and process measures of patients with confirmed infection (COVID-19) and non-infected patients (non-COVID-19) who underwent reperfusion therapies for acute ischemic stroke. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
10
1
Order By: Relevance
“…In line with our results, 2 previous small studies indicated an increased risk of bleeding complications after IVT and EVT in patients with COVID-19. 13,15 Given the increased risk of SICH in the IVT group, we also investigated whether bridging was associated with a higher risk of intracranial hemorrhage than DMT. In this subgroup analysis, patients undergoing DMT had a nonsignificant lower risk of hemorrhagic complications in comparison with bridging, despite a numerically lower risk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In line with our results, 2 previous small studies indicated an increased risk of bleeding complications after IVT and EVT in patients with COVID-19. 13,15 Given the increased risk of SICH in the IVT group, we also investigated whether bridging was associated with a higher risk of intracranial hemorrhage than DMT. In this subgroup analysis, patients undergoing DMT had a nonsignificant lower risk of hemorrhagic complications in comparison with bridging, despite a numerically lower risk.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding larger arteries and their recanalization, previous studies have reported inconsistent data concerning EVT revascularization results in patients with COVID-19, with successful recanalization ranging from 56% to 100% 9,[12][13][14]17,19 and first pass effect from 0% to 35.6%. 12,18 The procoagulant and proinflammatory states associated with COVID-19-related endothelial dysfunction 2 likely contribute to a higher clot burden and more difficult recanalization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the time from door to treatment showed no significant difference. According to some studies, the time to treatment was significantly prolonged in COVID-19 positive patients with AIS ( 25 , 28 ). Such a delay may be due to: the shortage of stroke team members, deceleration of evaluations, adherence to traffic restriction, and practice of preventive measures ( 33 ).…”
Section: Discussionmentioning
confidence: 99%